Blockchain – ICBC 2020 : third international conference, held as part of the Services Conference Federation, SCF 2020 Honolulu, HI, USA, September 18-20, 2020 Proceedings /: third international conference, held as part of the Services Conference Federation, SCF 2020 Honolulu, HI, USA, September 18-20, 2020 Proceedings. (2020) - Unknown
No abstract available